Protein expression in animal cells - Roth, Michael G. (Methods in cell biology, 1994)
Critically acclaimed for more than 25 years, the Methods in Cell Biology series provides an indispensable tool for the researcher. Each volume is carefully edited by experts to contain state-of-the-art reviews and step-by-step protocols. Techniques are described completely so that methods are made accessible to users.